2015
DOI: 10.17784/mtprehabjournal.2015.13.232
|View full text |Cite
|
Sign up to set email alerts
|

EMG frequency spectral characteristics of inspiratory accessory muscles during the shoulder lifting motion in throwing athletes

Abstract: Background: Dysfunctions related to the shoulder joint are very common in throwing athletes, due to the overhead generated in repetitive movements with your arms above your head. In addition, in handball, the movements are of high intensity, which generates a large metabolic demand and high ventilatory demands. Studies show that highest work of the respiratory muscles, coupled with high mechanical requirement in the upper limbs, generates a dual requirement under the inspiratory muscles in these athletes, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Following the above mentioned research, we believe that in handball, there is a high and double mechanical demand on inspiratory accessory muscles. This overload in throwing athletes has been also described by Hartz et al (2015) , and related to the high recruitment of the trunk and upper limb musculature during the sport-specific movements, high-contact situations and a high number of throws performed during a game ( Povoas et al, 2014 ). Consequently, improvement in inspiratory muscle conditioning may reflect a reduced mechanical demand and fatigue for inspiratory accessory muscles during intensive levels of handball game, which may be another factor associated with enhanced performance.…”
Section: Discussionmentioning
confidence: 96%
“…Following the above mentioned research, we believe that in handball, there is a high and double mechanical demand on inspiratory accessory muscles. This overload in throwing athletes has been also described by Hartz et al (2015) , and related to the high recruitment of the trunk and upper limb musculature during the sport-specific movements, high-contact situations and a high number of throws performed during a game ( Povoas et al, 2014 ). Consequently, improvement in inspiratory muscle conditioning may reflect a reduced mechanical demand and fatigue for inspiratory accessory muscles during intensive levels of handball game, which may be another factor associated with enhanced performance.…”
Section: Discussionmentioning
confidence: 96%
“…Asymmetry in muscle fatigability is certainly not limited to short track, however. Mastalerz et al [23] reported differences in myolectrical manifestations of fatigue between the muscles of the right and the left legs in runners, reaching from 12,5% to 26,5%, depending on the muscle Hartz et al measured the myolectrical manifestations of fatigue index through the induction of shoulder evation movement [24].…”
Section: Discussionmentioning
confidence: 99%
“…Mastalerz et al reported differences in fatigue between the muscles of the right and the left legs in runners, reaching from 12,5 % to 26,5 %, depending on the muscle [24]. Hartz et al measured the fatigue index through the induction of shoulder evation movement [25].…”
Section: Discussionmentioning
confidence: 99%